Penerapan Handout Dalam Model Pembelajaran Learning Cycle 7E untuk Meningkatkan Hasil Belajar Siswa - Rahmawati, Himmatul; Edie, Sukiswo Supeni; Khumaedi, Khumaedi (UPEJ Unnes Physics Education Journal, 2019)
Physics is a study of natural phenomena and its interactions. In learning physics, it is necessary to practice the concepts of physics in everyday life. However, physics is still considered as a difficult subject by most of the students. It leads to the low outcomes of students' cognitive learning outcomes. Learning model and teaching materials are needed, so that it will be easier for students to understand a lesson. In this study, the researcher used 7E Learning Cycle model with handouts. This study intended to determine the effects of handout as a learning media in 7E Learning Cycle model to improve the learning outcomes of VII Grade students of SMP Negeri 2 Demak on the lesson of measurement. The research method used in this research was experimental research method with Pretest-Posttest Control Group Design as the research design. The sample of this study was taken by cluster random sampling technique. It obtained research samples which were class VII D as the experimental class, and class VII A as the control class. Based on the result of the study, it obtained the average value of posttest of the experimental class was 73.50, and the control class was 58.31. The hypothesis testing by using point-biserial correlation coefficient and the coefficient of determination showed that handout as the learning media in 7E Learning Cycle model had a positive effect on students' cognitive learning outcomes. The improvement of student learning outcomes was indicated by the N-Gain test value of the experimental class of 0.26, and the control class of 0.10 with the low category. In conclusion, handout as the learning media in the 7E Learning Cycle model influences and improves student learning outcomes.